2015
DOI: 10.2166/wrd.2015.088
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biologically active GAC and complementary technologies for gray water treatment

Abstract: The reuse of gray water for applications ranging from irrigation to showering is a viable means to reduce net water demand when water supplies are stressed. The objective of this study was to investigate the treatment of gray water using biologically active granular-activated carbon (GAC) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Although the columns were not operated in duplicate in this study, IOBAC design and operation at 23 °C condition were similar to past IOBAC studies. Specifically, GAC columns had previously been operated for 6 months at the same temperature, at a similar design flux (e.g., 3.7-5.8 L min −1 m −2 ), and with the same seed population for the treatment of synthetic gray water 11 and municipal wastewater. 15 Those studies did not explore the efficacy of thermal swing, but provide a useful benchmark against which to compare 23 °C IOBAC performance in this study.…”
Section: Iobac and Ts-iobac Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the columns were not operated in duplicate in this study, IOBAC design and operation at 23 °C condition were similar to past IOBAC studies. Specifically, GAC columns had previously been operated for 6 months at the same temperature, at a similar design flux (e.g., 3.7-5.8 L min −1 m −2 ), and with the same seed population for the treatment of synthetic gray water 11 and municipal wastewater. 15 Those studies did not explore the efficacy of thermal swing, but provide a useful benchmark against which to compare 23 °C IOBAC performance in this study.…”
Section: Iobac and Ts-iobac Setupmentioning
confidence: 99%
“…Each experiment was performed continuously for at least three weeks. Although each column study was limited to 30 days of operation due to funding constraints, it has been observed in past studies that the IOBAC system equilibrated within 3 weeks and maintained performance for up to 6 months, both when treating gray water influent at bench scale 11 and when treating municipal wastewater at pilot scale. 15 During the wastewater loading step, peristaltic pumps delivered ambient temperature influent at a hydraulic loading rate of 1.5 L min −1 m −2 to each column for 5 h (Fig.…”
Section: Thermal Swing During Bioregenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellis & Wood (1985) recommends a minimum depth of 30 cm for filter media for efficient removal of different physicochemical and microbial parameters and hence, most studies utilized a minimum media depth of 30 cm (Aizenchtadt et al 2009;Zipf et al 2016;Thompson et al 2020;Sharaf & Liu 2021). However, a few studies while assessing the feasibility of compact systems used media depth of less than 30 cm (Griffioen & Natha 2013;Ward et al 2015;Prabha et al 2021). Removal of most of the contaminants occurs in the top 10-30 cm depth of filter media.…”
Section: Media Depthmentioning
confidence: 99%
“…Ward et al (2015) investigated the treatment of gray water using biological activated carbon (BAC) and complementary technologies. BAC performed well over test periods as long as six months.…”
mentioning
confidence: 99%